Analisis Rantai Pasok Dan Dayasaing Sapi Potong Lokal Di Sulawesi Selatan - Mappigau, Palmarudi; Upe, Jusni Ambo; Kasim, Kasmiati (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to analyze the relationship between the supply chain and the competitiveness of native beef cattle in South Sulawesi Province. A conceptual model was developed to examine how supply chains, including strategic supplier partnerships, market information sharing, and knowledge technology in beef cattle production sharing, are related to the competitiveness of native beef cattle. A survey questionnaire based on 64 farmers and intermediary traders from Bone Regency, South Sulawesi Province, was conducted to collect empirical data to test the formulated hypothesis. Spearman’s correlation coefficient analysis was conducted to test the hypothesized relationship. The study result showed that strategic supplier partnerships have a significant and positive relationship with competitive native beef cattle, while the market share of information and knowledge technology in beef cattle production was not significant and positively associated with competitive native beef cattle. The study’s limitations/implications are other important dimensions for supply chain partnerships, namely information sharing, goal congruence, decision synchronization, incentive alignment, and resource sharing should also be involved in future research. Since this study was limited to the province of South Sulawesi, the findings of this study cannot be generalized to supply chain practices in Indonesia and developing countries. Therefore future research should be carried out in other provinces in Indonesia or developing countries.